Closing the justice gap for adult and child sexual assault: rethinking the adversarial trial - Cossins, Anne (Palgrave Macmillan, 2020)
1. Introduction -- 2. The Nature and Effects Of Adversarialism: Jury Decision Making In Sexual Assault Trials -- 3. Factors That Predict Outcomes in Sexual Assault Trials -- 4. 'Commonsense' Or 'Life Experience': Jurors' Perceptions Of Guilt -- 5. 'No Means Yes And Yes Means Anal': The Cultural Climate In Which Sex Offences Are Prosecuted -- 6. The Nature And Effects Of Adversarialism . Sites Of Activation For Heuristic Reasoning Processes -- 7. Modernisation Of The Substantive Law Of Consent -- 8. Cross Examination In Sexual Assault Trials: Evidentiary Safeguard Or An Opportunity To Confuse? -- 9. Contemporary Reforms To Cross-Examination -- 10 . The Problems Facing Reformers Of The Sexual Assault Trial -- 11. Achieving Best Evidence For Vulnerable Witnesses: The Use Of Trauma-Informed Theory To Reform The Sexual Assault Trial -- 12. Reform Measures: The Devil Is In The Detail.